Śrī Veṅkaṭēśvara darśanamu - Rāmakiruṣṇamūrtti, Timmarājū Visvapati (Śrī Ḍijains, 2007)
A book explaining the glory of Lord Sri Venkateswara through 24 names of Lord Srimannarayana called kesava namams
Keywords: Telugu-Sprache; Religiöse Literatur; Geschichte 2000-2100; Venkateshvara